Acoustic behaviour of polychoirs in the Baroque church of Santa María Magdalena, Seville. (April 2021) - Alberdi, E.; Galindo, M.; León-Rodríguez, A.L.; León, J.
Highlights: The use of Baroque church polychoirs was recreated via acoustic simulation technique. Upper choir and organ performing in unison provide a better subjective reverberation. Organ position was the most appropriate for music performance in this Baroque church. The use of polychoirs improves the subjective noise level in a Baroque church. Use of polychoirs homogenize the acoustic parameter ranges, except for EDT. Abstract: In addition to its other virtues, Baroque music was a means of expression and representation of the spirit of the Counter-Reformation, introducing an aesthetic which revealed theatricality, drama and splendour. The polyphonic style of the Renaissance gave way to a polychoral style, with the presence of several choirs or instruments placed in different locations within the church (cori spezzati). The aim of this study is to recreate the use of polychoirs, using simulation techniques in the Baroque Church of Santa María Magdalena, Seville, after testing the acoustic model in CATT-Acoustic software. The research shows that only the execution in unison of the upper choir and organ sound sources positions provides an equivalent sensation of musical and oral clarity and a better subjective reverberation than the other combinations. However, the use of different combination of sound sources positions worsens the overall sound sensation compared to the sound/music emitted from the position of organ alone.